1998
DOI: 10.1128/jcm.36.7.2157-2163.1998
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Hormonema dematioides Peritonitis in a Patient on Continuous Ambulatory Peritoneal Dialysis: Criteria for Organism Identification and Review of Other Known Fungal Etiologic Agents

Abstract: We report a fatal case a fungal peritonitis caused by the yeast-like dematiaceous mould Hormonema dematioides in a 45-year-old woman. The woman had a 13-year history of insulin-dependent diabetes mellitus and had been on continuous ambulatory peritoneal dialysis for chronic renal failure. H. dematioides was repeatedly isolated from the dialysate culture specimens collected on days 3, 9, 16, and 20 of her hospital stay. Preliminary culture reports on day 7 of the growth of a yeast-like fungus, a probableCandida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 68 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…These comprise mainly bone and joint infections and peritonitis. Recommendations can be found in Table .…”
Section: Recommendations By Clinical Entitiesmentioning
confidence: 99%
“…These comprise mainly bone and joint infections and peritonitis. Recommendations can be found in Table .…”
Section: Recommendations By Clinical Entitiesmentioning
confidence: 99%
“…Another species of invasive mould, Aspergillus terreus , although widely found in the environment, is a rare human pathogen, with just one case having been reported in PD (18). Shin et al (19) reported a first case of FP due to Hormonema dematioides and provided microbiologists with criteria for differentiating this organism from the similar mould Aureobasidium pullulans and from various other yeast genera.…”
Section: Causative Organisms In Fpmentioning
confidence: 99%
“…Another species of invasive mould, Aspergillus terreus, although widely found in the environment, is a rare human pathogen, with just one case having been reported in PD (18). Shin et al (19) reported a first case of FP due to Hormonema dematioides and provided microbiologists with criteria for differentiating this organ- (34), Exophiala jeanselmei, Drechslera spicifera, and Fusarium species (2) have also been reported in patients receiving PD. An unusual case of Rhizopus microsporus (mucormycosis) fungal infection in a teenage boy on continuous ambulatory peritoneal dialysis (CAPD) has been described (35,36).…”
Section: Causative Organisms In Fpmentioning
confidence: 99%
“…Common yeast-like fungi include Candida, Trichosporon , and Cryptococcus . Filamentous fungi are rare in FP and include Aspergillus, Rhizopus , and Histoplasma ( 8 ). In this study, 7 (63.6%) cases were caused by Candida and Candida parapsilosis was the most common pathogen, accounting for 5 FP cases (45.5%), while other fungi are less common.…”
Section: Discussionmentioning
confidence: 99%